OPTIMISASI STRUKTUR TOWER BERBASIS ELEMEN HINGGA - ARHAMI
Abstract : This study concerned with optimization of a space structure. The structure of the tower in this study is modeled as a space truss. The optimization method used is categorized as optimization with constraints. The finite element method is used to analyze the structure to obtain nodal displacement, internal forces and induced stress for each structural member. In this research the fully stress design method (FSD) is used for optimization technique because the algorithm is simple and straightforward and it is easy to apply for some engineering design problems such as a tower. Although the method is earlier than the current optimization technique, it is still the most popular used for truss structural analysis. Fully stress design is sought by multiplying the design variables by the ratio of the current variable with the constraint limit. The objective function is the weight of the structure, hence the result of the optimization process is the minimum weight satisfying the chosen constraints. The design variables are the cross-sectional area of the bar. The external forces are caused by structural weight, wind forces and dish load. The internal stresses of each member should not higher than the yield strength for the tension member, whereas the compression member have two constraints namely the buckling strength and the yield strength. In this study the value of the yield strength for tension members are different with the yield strength for compression load. The side constraint for all design variables are that the cross sectional area of each member should be greater than zero. The other side constraint is making several groups of member cross sectional area to resemble real conditions in the field .